If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26=4k-2
We move all terms to the left:
26-(4k-2)=0
We get rid of parentheses
-4k+2+26=0
We add all the numbers together, and all the variables
-4k+28=0
We move all terms containing k to the left, all other terms to the right
-4k=-28
k=-28/-4
k=+7
| 2x(7x-1)=0 | | y+0.1y=3 | | -2.7=c-2.6 | | 2p-6=18 | | 25-3b=16 | | 6(2x=4)-3(2x+3)=45 | | N-2n+10=16 | | 6=z-25/9 | | 6(2x=4)-3(2x=3)=4= | | f+16/4=7 | | r-12=96 | | 5(y-73)=35 | | 6(2x=4)-3(2x=3)=45 | | 19=y/3+15 | | 3x+27=6x | | 5(x=4)=2(x-3)=42 | | 5(x+5)-(8x-5)=51 | | 8+4d=84 | | z-25=6/9 | | 7(g+5)=77 | | 2x+17/3=9 | | 7x^-12x+6=0 | | 8s+3=99 | | 5(3x=4)=4(2x-2)=127 | | 7x2-12x+6=0 | | 4(v-58)=88 | | 73=-4(x-2)-3(6x-7) | | 7=13-2r | | 1/18x=0 | | 48=3+5y | | 5x/7+x/4=3 | | 8x²-8x+2=0 |